Pengaruh ICT Literacy dan Dukungan Teman Sebaya Terhadap Self Directed Learning Pada Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2022 - Aryanti, Arini; Gumilar, Rendra; Nurdianti, Raden Roro Suci (LPPM Institut Pendidikan Nusantara Global, 2024)
This research was motivated by the problem of low levels of self-directed learning among students. This research was carried out to determine the influence of ICT literacy and peer support on self-directed learning in students majoring in Economic Education, Class of 2022, partially and simultaneously. This research uses a quantitative survey method. The population in this study were all Economic Education students at the Faculty of Teacher Training and Education, Siliwangi University class of 2022. The sampling technique used was